Valley of volcanoes in Andahua, geopark in southern Peru project - Zavala Carrión, Bilberto Luis (2010)
The Instituto Geológico Minero y Metalúrgico – INGEMMET has developing studies in areas of geological significance to promote the establishment of Geoparks. Some of these areas stand out for their geodiversity and volcanic landscape. One of them was denominated a natural wonder of Perú and is the Volcanoes’s Valley of Andahua. The Volcanoes’s Valley of Andahua, is located 135 km from Arequipa, the second most important city of Perú. The geopark’s area has altitudes between 1350 masl (Colca Canyon) and 5450 masl (Chila’s Mountains). Here are located five districts of Castilla province with 13 000 people approximately. Its economy is based on agriculture, cattle, mining and fishing activities. Volcanic activity developed during Pliocene, Pleistocene and Holocene, originated in the valley floor and hillsides, volcanic emissions and fissure-type products and Strombolian eruption. Fields of andesitic-basaltic lavas, 24 cinder/scoria cones, are superposed on alluvial fans of Upper Pleistocene, and a complex geological history comes from Jurassic. Geomofologic, tectonic and hydrogeolgic sceneries, sedimentary and igneous rocks and important epithermal deposits, are so important in the area because they had given the economic life for decades. Lakes or natural dams caused by lavas, canyons and waterfalls, resurgence of water and hot springs, mountains and structural hills, ancient strato-volcanoes and in general a domain of volcanic landscape. Increase the potential of the geopark, some pre-hispanic occupation remains, pre-Inca and Inca’s agricultural production centers, diversity flora and fauna, ancestral ways and customs of their communities. This majestic valley offers us their geodiversity, fertile grounds, culture and allows us to understand the volcanic hazards. To know, protect and do it sustainable with the help of the people from Alto Castilla, allow in a short time its postulation as Geopark, its geoconservation and convert Andahua into an important tourist destination.